Composite bone cements loaded with a bioactive and ferrimagnetic glass-ceramic. Part I: Morphological, mechanical and calorimetric characterization. (August 2014) - Bruno, Matteo; Miola, Marta; Bretcanu, Oana; Vitale-Brovarone, Chiara; Gerbaldo, Roberto; Laviano, Francesco; Verné, Enrica
Hyperthermia is a technique for destroying cancer cells which involves the exposition of body's tissue to a controlled heat, normally between 41℃ and 46℃. It has been reported that ferro- or ferrimagnetic materials can heat locally, if they are placed (after being implanted) under an alternating magnetic field, damaging only tumoral cells and not the healthy ones. The power loss produced by the magnetic materials can be dissipated in the form of heat. This phenomenon has to be regulated in order to obtain a controlled temperature inside the tissues. The material that was produced and characterized in this work is composed of two phases: a polymethylmethacrylate (PMMA) matrix in which a ferrimagnetic biocompatible/bioactive glass ceramic is dispersed. This composite material is intended to be applied as bone filler for the hyperthermic treatment of bone tumors. The ferrimagnetic bioactive glass-ceramic belongs to the system SiO2 –Na2 O–CaO–P2 O5 –FeO–Fe2 O3 and contains magnetite (FeO*Fe2 O3 ) inside an amorphous bioactive residual phase. The composite material possesses structural, magnetic and bioactivity properties. The structural ones are conferred by PMMA which acts as filler for the bone defect or its damaged area. Bioactivity is conferred by the composition of the residual amorphous phase of the glass-ceramic and magnetic properties are conferred by magnetite crystals embedded in the bioactive glass-ceramic. The characterization involved the following tests: morphological and chemical characterization (scanning electron microscopy–energy dispersion spectrometry–micro computed tomography analysis), calorimetric tests and mechanical test (compression and flexural four point test). In vitro assessment of biological behavior will be the object of the part II of this work.